2008
DOI: 10.1016/j.nuclphysb.2008.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of the twisted superconducting semilocal strings

Abstract: We study the stability properties of the twisted vortex solutions in the semilocal Abelian Higgs model with a global SU(2) invariance. This model can be viewed as the WeinbergSalam theory in the limit where the non-Abelian gauge field decouples, or as a two component Ginzburg-Landau theory. The twisted vortices are characterized by a constant global current I, and for I → 0 they reduce to the semilocal strings, that is to the AbrikosovNielsen-Olesen vortices embedded into the semilocal model. Solutions with I … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…[40,41,47,48,49]. It has been shown that in the semi-local model for β > 1, the instability of the embedded ANO vortex corresponds to its bifurcation with a oneparameter family of solutions, which are, however, still unstable [50,51,52,53]. The existence of a lowest energy limit of this family of solutions with a less symmetric potential has been demonstrated in Ref.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…[40,41,47,48,49]. It has been shown that in the semi-local model for β > 1, the instability of the embedded ANO vortex corresponds to its bifurcation with a oneparameter family of solutions, which are, however, still unstable [50,51,52,53]. The existence of a lowest energy limit of this family of solutions with a less symmetric potential has been demonstrated in Ref.…”
mentioning
confidence: 86%
“…The SU(2) symmetric case, has been considered in Ref. [50,51,52]. Here, the Lagrangian of the theory, Eq.…”
Section: Linear Perturbations and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The SU(2) symmetric model, called semilocal has been considered in Refs. [29,30,31,32,33,34,42,43,44].…”
Section: The Two Component Ginzburg-landau Theorymentioning
confidence: 99%
“…In the case of the twisted semilocal vortices of Ref. [17], with ω α timelike, such deformations indeed exist [21], however, they correspond to the same type of instability as those of ANO vortices embedded in a two-component extended Abelian Higgs model [22]. In the present case, however, such potential instabilities are absent.…”
Section: Twisted Coincident Composite Vorticesmentioning
confidence: 47%